Inclusion levels of insect flour (Tenebrio molitor) in Nilo tilapia diets in recirculation tanks (Research, Society and Development, 2023)
The objective of this research was to determine inclusion levels of insect mealworms in Nile tilapia fingerlings feeding. A total of 225 tilapia fingerlings (0.61 ± 0.12 g) distributed in 15 tanks (30 L) installed in a completely randomized design with five treatments (0% or control). 5, 10, 15 and 20% mealworms) with three repetitions. Feeding rates were defined from weekly biometrics and periodic monitoring of water physicochemical parameters was performed. Regression models were applied to determine the best zootechnical response dose. The results of the physicochemical parameters of the water during the experiment were adequate for the species. There was no difference between inclusion levels for final weight, weight gain, feed intake, survival, productivity, condition factor and hepatosomal index. The inclusion of mealworms in Nile tilapia fingerlings promoted a linear increase in apparent feed conversion. There was an increasing linear effect for the viscerosomatic index. It is suggested a maximum inclusion limit of tenebrio mealworms in tilapia fingerling of 15%, due to the presence of antinutritional factors such as chitin.